State-resolved studies of CO2 sticking to CO2 ice - Jansen, Charlotte; Juurlink, Ludo B. F. (Frontiers in Chemistry, 2023)
Internal vibrations may affect the adsorption, scattering, and reactions of molecules impinging onto a surface. The energy of the ν 3 antisymmetric stretch vibration of CO 2 slightly exceeds the desorption energy of CO 2 bound to CO 2 ice. We use supersonic molecular beam techniques and rovibrationally state-resolved excitation to determine whether this vibration affects condensation of gas phase CO 2 to its ice. We detect sticking and CO 2 ice formation using RAIRS and quantify the sticking probability using the King & Wells method with modulation of the vibrational excitation and Fourier transform based detection. We find that the influence of this vibration on the structure of the formed ice and on the sticking probability is negligible under our conditions. Based on our detection limit, we quantify the weighted average sticking probability at approximately 0.9 and the difference between the state-resolved and weighted average sticking probability as below 0.03%.